Diversity, representation, and the limits of engaged pluralism in (economic) geography. (June 2020) - Rosenman, Emily; Loomis, Jessa; Kay, Kelly
Within geography writ large, and economic geography in particular, there has been increasing interest in 'engaged pluralism' – defined by its proponents as lively and respectful engagement across theoretical, methodological, and topical lines – to increase diversity and build mutual respect among scholars. Drawing on feminist and postcolonial scholarship, we offer a sympathetic critique of engaged pluralism, grounded in a review of publishing trends in economic geography. Our findings reveal theoretical inertia around particular topics and paradigms, as well as low rates of publishing participation from women. We close with a discussion of engagement, reciprocity, and meaningful contact.